Major cardiac risk factor screening and the role of exercise in preventing CHD - Morris, Alfred F.; Healthy Learning Videos (Monterey, CA : Healthy Learning, 2007)
Major Cardiac Risk Factor Screening and the Role of Exercise in Preventing CHD reviews the eight major cardiac risk factors facing all individuals. The presentation also explains how health/fitness professionals can screen prospective clients for coronary heart disease (CHD). Finally, in a straightforward manner, the presentation details how health/fitness professionals can properly address CHD screening data with their clients, before their clients initiate an exercise program.
Title from resource description page (viewed July 07, 2016).
In English.
Keywords: Coronary heart disease -- Diagnosis; Coronary heart disease -- Exercise; Coronary heart disease -- Diagnosis; Educational films; Nonfiction films; Educational films; Nonfiction films; Films éducatifs.; Films autres que de fiction